Structural characterization of T-protein of the Escherichia coli glycine cleavage system by X-ray small angle scattering - (:unkn) unknown (My University, 2003)
T-protein, one of the components of the glycine cleavage complex, catalyses the formation of ammonia and methylene-tetrahydrofolate from H-protein-bound intermediate. Native T-protein of the glycine cleavage system from E. coli was efficiently purified using a combination of hydrophobic interaction, gel permeation and ion exchange chromatography. Synchrotron radiation small angle X-ray solution scattering indicates that T-protein has an extended structure in solution. A low resolution model of the protein was constructed ab initio and tentative models of the tertiary structure were built using prediction methods constrained by the scattering data.
Keywords: Models, Molecular; Escherichia coli; Escherichia coli Proteins; Aminomethyltransferase; Chromatography; Hydroxymethyl and Formyl Transferases; Protein Structure, Tertiary; Scattering, Radiation; X-Rays